Pembuatan Gula Semut dari Gula Merah Kelapa di Kabupaten Bulukumba - Diana Eka Pratiwi; Army Auliah; Maryono Maryono (Universitas Negeri Makassar, 2019)
Herlang Subdistrict is the largest producer of coconut juice (along with Selayar Regency and JenepontoRegency) which is the raw material for coconut sugar production in South Sulawesi. Tugondeng Village is one ofthe villages in Herlang District. About 80% of Tugondeng villagers work in the coconut sugar manufacturingindustry. However, this potential has not well developed due to the low economic value of brown sugar. To increasethe selling price of coconut sugar produced by Tugondeng Village, efforts need to be made to process coconut sapand coconut sugar into products which have higher selling price, namely palm sugar. The steps taken to achieve theobjectives of this activity were : (a) presentation of material on how to process coconut sap and coconut sugar intopalm sugar; and (b) demonstration of preparing palm sugar from coconut sap and coconut sugar. The resultsobtained show that the process of making palm sugar from coconut sap and coconut sugar is quite simple and thepalm sugar produced has longer shelf-life than coconut sugar